Influence of IT Application to Organizational Performance mediated by warehouse management and customer relationship management - Olivia Gisena Santoso; Hotlan Siagian (Petra International Journal of Business Studies, 2019)
In this thesis discuss about the affect of Information Technology Application to Organizational Performance through Warehouse Management and Customer Relationship Management on company. In this study using primary data with a population of 109 companies and 52 samples of companies using data collection methods, namely 5 points Likert scale in the form of questionnaires distributed in companies that are groups on third party logistic companies in Surabaya and Sidoarjo. This study uses Structural Equation Modeling analysis techniques, also called path modeling with SmartPLS tools. The questionnaire collected was 53 questionnaires. The result showed that the affect of Information Technology Application on Organizational Performance were positive and significant. In addition, the results also showed that the affect of Information Technology Application on Warehouse Management were positive and significant, the result showed that the affect of Information Technology Application on Customer Relationship Management were positive and significant, the result also showed that the affect of Warehouse Management on Organizational Performance were positive and significant, and the result showed that the affect of Customer Relationship Management on Organizational Performance were positif and significant in 3PL companies in Surabaya and Sidoarjo